Development of an Online Sales Information System for SMEs Using Incremental Methods - Habib, Ahmad; Kartika W. H., Andrey (Universitas Nusantara PGRI Kediri, 2020)
Home Industry Shoes is one of the SMEs that are engaged in the production and sale of shoes. Shoes SMEs in marketing and sales have been still relying on customers from surrounding areas of production activities. Current business competition is stringent, thus making SME shoes demanded to be more advanced in marketing and sales to be able to stay afloat. Shoes SMEs have problems with promotional media and sales, which does not yet have an independent online sales system. Therefore, the authors feel the need to help SMEs by creating an online sales information system that can be used as a promotional media as well as a media for selling independently and easy to use. In this study, the authors apply the incremental method in system development and also observation in gathering data on the needs of the system developed. Achievements in this study, the authors, produce an online sales information system for SMEs, in particular, the production of home industry shoes that can be used independently by SMEs to carry out promotions and sales online.